2000
DOI: 10.4269/ajtmh.2000.62.670
|View full text |Cite
|
Sign up to set email alerts
|

Severe anemia in young children after high and low malaria transmission seasons in the Kassena-Nankana district of northern Ghana.

Abstract: Abstract. Malaria and anemia accounted for 41% and 18% respectively of hospital deaths in the Kassena-Nankana district of northern Ghana during 1996. We measured hemoglobin (Hb), malaria prevalence, and anthropometric indices of 6-24-month-old infants and young children randomly selected from this community at the end of the high (May-October, n ϭ 347) and low (November-April, n ϭ 286) malaria transmission seasons. High transmission season is characterized by rainfall (the equivalent of 800-900 mm/yr.), while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 7 publications
6
52
0
Order By: Relevance
“…The relatively brief respite in transmission between February and May appeared sufficient to allow recovery of most severe anemia to above the 6.0 g/dl level. The work reported here and by Koram and others 10 demonstrates the need for longitudinal studies of seasonal risk of severe anemia in northern Ghana.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The relatively brief respite in transmission between February and May appeared sufficient to allow recovery of most severe anemia to above the 6.0 g/dl level. The work reported here and by Koram and others 10 demonstrates the need for longitudinal studies of seasonal risk of severe anemia in northern Ghana.…”
Section: Discussionmentioning
confidence: 54%
“…The infants and young children in these studies showed dramatic distinctions with respect to the prevalence of severe anemia as seen at enrollment at the end of the dry and wet seasons. 10 In effect, an epidemic of severe malarial anemia occurred in these children as the wet season progressed: apparently starting at 1% in May and increasing to 24% in October. Given the fact that we have now documented that intense transmission continues at least to February, the prevalence of severe anemia may even worsen relative to the 25% rate measured in October.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism we propose here may be a major contributor to the anemia seen in children in Africa at the end of the intense transmission season. 23 If this is the case, it will be extremely important to monitor hemoglobin status during trials of malaria vaccines that are designed not to prevent blood stage infection, but rather to limit it. 24 this study.…”
Section: Discussionmentioning
confidence: 99%
“…1 In areas with intense Plasmodium falciparum transmission, severe malarial anemia is the primary symptom of serious malarial disease among children less than two years of age and accounts for more than half of all malarial deaths in African children. 2,3 In malariaendemic areas, anemia is usually multifactorial in origin, but P. falciparum infection is the major factor in the etiology of severe anemia. 3 In areas of stable malaria transmission, anemia appears in the first few months of life, and has the highest prevalence towards the end of the first year.…”
Section: Introductionmentioning
confidence: 99%